Accelerated workflow for primary jaw reconstruction with microvascular fibula graft - Goetze, Elisabeth (3D Print Med, 2017)
INTRODUCTION: Major facial defects due to cancer or deformities can be reconstructed through microvascular osteocutaneous flaps. Hereby CAD/CAM workflows offer a possibility to optimize reconstruct and reduce surgical time. We present a retrospectiv observational study regarding the developement of an in-house workflow allowing an accelerated CAD/CAM fibula reconstruction without outsourcing. CASE DESCRIPTION: Workflow includes data acquisition through computertomography of head and legs, segmentation of the data and virtual surgery. The virtual surgery was transferred into surgical guides and prebent osteosynthesis plate. Those were sterilized and used in surgery. EVALUATION: The workflow was used in 30 cases. Minimum planning period took 4 days from CT to surgery, average time was 8 days. Planning could be transferred to surgery every time. Intraoperative complications regarding osteotomy, assembly and fixation did not occur. DISCUSSION/CONCLUSION: An in-house workflow for CAD/CAM fibula reconstruction is feasible within a few days providing an accelerated procedure even in urgent cases.